The Negative Relationship between Reasoning and Religiosity Is Underpinned by a Bias for Intuitive Responses Specifically When Intuition and Logic Are in Conflict - Daws, Richard E.; Hampshire, Adam (Frontiers in Psychology, 2017)
It is well established that religiosity correlates inversely with intelligence. A prominent hypothesis states that this correlation reflects behavioural biases towards intuitive problem solving, which causes errors when intuition conflicts with reasoning. We tested predictions of this hypothesis by analysing data from two large-scale Internet-cohort studies (combined N=63,235). We report that atheists surpass religious individuals in terms of reasoning but not working-memory performance. The religiosity effect is robust across sociodemographic factors including age, education and country of origin. It varies significantly across religions and this co-occurs with substantial cross-group differences in religious dogmatism. Critically, the religiosity effect is strongest for tasks that explicitly manipulate conflict; more specifically, atheists outperform the most dogmatic religious group by a substantial margin (0.6 standard deviations) during a colour-word conflict task but not during a challenging matrix-reasoning task. These results support the hypothesis that behavioural biases rather than impaired general intelligence underlie the religiosity effect.